Structural Evidence for Inter-Residue Hydrogen Bonding Observed for Cellobiose in Aqueous Solution - O'Dell, William B.; Baker, David C.; McLain, Sylvia E. (PLOS ONE, 2012)
The structure of the disaccharide cellulose subunit cellobiose (4-O-β-D-glucopyranosyl-D-glucose) in solution has been determined via neutron diffraction with isotopic substitution (NDIS), computer modeling and nuclear magnetic resonance (NMR) spectroscopic studies. This study shows direct evidence for an intramolecular hydrogen bond between the reducing ring HO3 hydroxyl group and the non-reducing ring oxygen (O5′) that has been previously predicted by computation and NMR analysis. Moreover, this work shows that hydrogen bonding to the non-reducing ring O5′ oxygen is shared between water and the HO3 hydroxyl group with an average of 50% occupancy by each hydrogen-bond donor. The glycosidic torsion angles φH and ψH from the neutron diffraction-based model show a fairly tight distribution of angles around approximately 22° and −40°, respectively, in solution, consistent with the NMR measurements. Similarly, the hydroxymethyl torsional angles for both reducing and non-reducing rings are broadly consistent with the NMR measurements in this study, as well as with those from previous measurements for cellobiose in solution.